2012
DOI: 10.1177/1076029612437578
|View full text |Cite
|
Sign up to set email alerts
|

Antiphosphatidylserine/Prothrombin Antibodies (aPS/PT) as Potential Markers of Antiphospholipid Syndrome

Abstract: The antiphospholipid antibodies present in antiphospholipid syndrome (APS) are directed at a number of phospholipid-binding proteins: b 2 glycoprotein I (b 2 GPI), prothrombin, and so on. Antibodies directed at b 2 GPI are accepted as a classification criterion for APS, while the presence of antiprothrombin antibodies is not. In the present article, we investigated the possible role of antiphosphatidylserine/prothrombin antibodies (aPS/PT) as marker of APS on a cohort of 295 individuals with APS (95 primary AP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 24 publications
5
43
0
Order By: Relevance
“…Correlation between aPS/PT and LA activity has been reported previously [7, 13, 33, 37] and our current study confirmed a strong correlation between aPS/PT and LA activity. IgG/IgM aPS/PT were the highest independent risk factors for LA activity with an OR > 12.9 as compared to aCL and anti- β 2 GPI with an OR < 9.0.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Correlation between aPS/PT and LA activity has been reported previously [7, 13, 33, 37] and our current study confirmed a strong correlation between aPS/PT and LA activity. IgG/IgM aPS/PT were the highest independent risk factors for LA activity with an OR > 12.9 as compared to aCL and anti- β 2 GPI with an OR < 9.0.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, aPS/PT antibodies were not strong independent risk factor for arterial thrombosis. Similarly, Vlagea et al found no association between the presence of aPS/PT and arterial thrombosis [33]. Two previous studies [7, 8] have shown anti-prothrombin antibodies as an independent risk factor for arterial thrombosis, but other reports [6, 9, 34] presented their data without differentiating between arterial or venous thromboembolic events.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have investigated the implications of aPT-A in the clinical manifestation of APS with controversial results [3][4][5][6]. On the other hand, several groups have reported that the presence of aPS/PT strongly correlates with that of LA and that aPS/PT were highly specific for the diagnosis of APS [7][8][9][10][11]. However, the clinical applicability and diagnostic utility of aPS/PT testing have not yet been fully defined mainly as a result of the lack of a standardized procedure to test aPS/PT and the low reproducibility of the results between laboratories.…”
Section: Introductionmentioning
confidence: 99%
“…aPT: anti-prothrombin; β2GP1: β-2-glycoprotein 1, NA; non-applicable. and significant associations have been reported in several autoimmune diseases [28][29][30][31][32][33][34][35][36]. Yang et al [26] demonstrated the aPT antibodies with prothrombinase activity and suggested that these catalytic aPT antibodies might contribute to thrombosis observed in APS patients.…”
Section: Discussionmentioning
confidence: 99%